Operation of the EWS in the city of Matagalpa, Nicaragua - Díaz López, Marjorie (2016)
The city of Matagalpa, due to the geological and morphological features of the territory, exposure to natural phenomena, the degradation of natural resources and rapid population growth, has endangered the welfare of its population, because of the high vulnerability and risk to the occurrence of natural disasters, principally flooding from the Grande Matagalpa River, which crosses through the center of the city, frequently leaving significant material damage and human loss. In this context, the initiative from the municipal government of Matagalpa to implement the “Rio Grande Matagalpa” project was born, financed by the European Cooperation, in order to initiate a process of flood risk management in the upper river basin and to strengthen and empower the population and the community in the prevention, mitigation and preparation against floods. As part of the project, the Joint Early Warning System (EWS) was designed, implemented and is currently operating, its purpose being to have available the information in real time, provided by automated tools and equipment, and monitored by local community organizations. The EWS is integrated into the risk management process which allows it to alert and communicate to the population about the possible occurrence of phenomenon possibly causing natural disasters, principally flooding in the city of Matagalpa.